Urban Regeneration and Hegemonic Power Relationships - Turkun, Asuman (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2011)
This paper aims to analyse the growing power of the urban coalition that has become dominant after the 2000s in Turkey. It is observed that the actors of the central and local governments as well as the authorities of important state institutions have become part of this coalition with the same hegemonic neo-liberal discourse especially related to urban transformation driven by the motive of increasing urban land rents and real-estate development. This discourse and the accompanying implementations have also been strongly supported by the private-sector actors, such as developers, land owners, advisors, professionals, and the leading media. The power of this coalition has been enhanced by means of changes made in current laws and enactment of new laws as well as the increasing initiative of particular state institutions, such as the Mass Housing Development Administration (TOKI.) and Privatization Administration. This paper also aims to discuss the spatial implications of the top-down decisions given by this powerful coalition especially in Istanbul, a city that poses to be a complete laboratory reflecting the ongoing trends in the economic and political spheres and a clear picture of the changing socio-spatial structure. The vision of the city as a centre of international finance, service and tourism appears to guide the new urban policies after 2000. As a result, the importance of urban areas that have high rent-gaining potential has increased, leading to a growing pressure on squatter housing areas and the historic urban centres populated by the urban poor.
Keywords: Public Administration